Mekanisme Penyelesaian Sengketa Pemilihan Umum di Indonesia - Benni Erick; M. Ikhwan (Jurnal Analisis Hukum, 2022)
This study describes the resolution of general election disputes in Indonesia. Elections should be a democratic party filled with enjoy, starting from preparation, and implementation to receiving election results through a process with integrity. However, the opposite is possible, so it is necessary to explain the mechanism for resolving general election disputes. This paper uses a library research method and is a normative juridical legal research with secondary data such as books, journals, and other documents used as the main data using a statute approach. From the research conducted, it is concluded that: First, the general election is a means of people's sovereignty to elect members of the People's Representative Council (DPR), members of the Regional Representatives Council (DPD), President and Vice President, and to elect members of the Regional People's Representative Council (DPRD). which is carried out directly, publicly, freely, confidentially, honestly, and fairly within the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Second, the dispute resolution of the election process can be carried out through the General Elections Supervisory Agency or abbreviated as Bawaslu, and through the State Administrative Court. However, disputes over election results can only be resolved through the Constitutional Court. Third, the resolution of process disputes and outcome disputes can be followed by mediation and adjudication procedures.